-6*2+k=-20

Simple and best practice solution for -6*2+k=-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6*2+k=-20 equation:



-6*2+k=-20
We move all terms to the left:
-6*2+k-(-20)=0
We add all the numbers together, and all the variables
k+8=0
We move all terms containing k to the left, all other terms to the right
k=-8

See similar equations:

| -0.3z=-0.93 | | 3p=4p+7 | | 15a-10=-3(-5a+2) | | 3a+11=7a-13 | | -4=a/3-6 | | 1=4c+3 | | (5x+28)=(4x+31) | | 7e+3.3=6 | | -2(5-b)+2b=-6 | | 6x+2=4x–8 | | 2)/2=6(x+3)/12 | | 5x-8=3x+2 | | 10x/7=5 | | x+1+19=4x-7 | | 8(7x+3)-5x=75 | | V-6v=-20 | | 19/n-9=6/5 | | -3x-100=-10x+30 | | n+0.9=3.6 | | -5h=11/3 | | 4d=-20* | | 2x+5-3x=40+8 | | 6(x-2)/2=6(x+3)/2 | | 1.4x+5.3x-4=2-1.12x | | 10=6+4r-5r | | 34x+180=90 | | 6n-4=-7n-4 | | -3(p+3)-5=-14-3p | | 20+4=-4(4x-6) | | -46+23=46t+23 | | 3x+x+2=6x-2x=6 | | x+4+13x=18 |

Equations solver categories